Analisis Risiko Pasar Saham Syariah JII dengan Value at Risk dan Expected Shortfall - Siti Lailatul Mafruhah; Imam Tamami; Didik Fathul Qorib (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study measures market risk in the Jakarta Islamic Index (JII) portfolio by comparing Value at Risk (VaR) and Expected Shortfall (ES). Daily return data from 2020–2025 exhibit extreme leptokurtic distribution (kurtosis >12), making the normality assumption underlying VaR inadequate. The findings reveal that ES, particularly under the Historical Simulation approach, provides more conservative and realistic risk estimates than VaR. At the 99% confidence level, ES captures an average extreme loss of IDR 48 million, substantially higher than VaR predictions. These results highlight ES as a more appropriate risk metric for Sharia-compliant investors, especially in stress testing and risk capital allocation.